Energy input-output relationship of cropping systems - SINGH, M K; PAL, S K; THAKUR, R; VERMA, U N (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1983-90 at Ranchi, to study the energetics of 4 cropping systems, viz maize (Zea mays L.) -wheat (Triticum aestivum L. emend. Fiori & Paol.), soybean [Glysine max(L.) Merr.] -wheat, rice (Oryza sativa L.) - wheat and groundnut (Arachis hypogaea L.) - wheat. Maize produced significantly higher grain and total biomass energy (34 332 and 130 394 MJ/ha respectively) than the other rainy season (kharif) crops. Wheat grown in sequence after soybean or groundnut produced higher energy from grain and total biomass than after maize or rice. Among cropping systems, groundnut-wheat sequence was most efficient in energy production through grain (321 MJ/ha/ day), followed by maize-wheat (318 MJ/ha/day). But in terms of total biomass, maize-wheat sequence was more efficient (923 MJ/ha/day), followed by groundnut-wheat (609 MJ/ha/day).